Problem solving for management : a new look at method study - Raybould, E. B; Minter, Alfred Lawrence (London : Institute of Practitioners in Work Study, Organisation and Methods, 1971)
The main theme of the book is conscious development of the purposeful thinking which is required in almost all practical situations.
Includes bibliography
ucj 16/01/2019
Loan
Keywords: Management; Problem solving